Bouillonamide: A Mixed Polyketide–Peptide Cytotoxin from the Marine Cyanobacterium Moorea bouillonii - Tan, Lik Tong (MDPI, 2013)
The tropical marine cyanobacterium, Moorea bouillonii, has gained recent attention as a rich source of bioactive natural products. Continued chemical investigation of this cyanobacterium, collected from New Britain, Papua New Guinea, yielded a novel cytotoxic cyclic depsipeptide, bouillonamide (1), along with previously reported molecules, ulongamide A and apratoxin A. Planar structure of bouillonamide was established by extensive 1D and 2D NMR experiments, including multi-edited HSQC, TOCSY, HBMC, and ROESY experiments. In addition to the presence of α-amino acid residues, compound 1 contained two unique polyketide-derived moieties, namely a 2-methyl-6-methylamino-hex-5-enoic acid (Mmaha) residue and a unit of 3-methyl-5-hydroxy-heptanoic acid (Mhha). Absolute stereochemistry of the α-amino acid units in bouillonamide was determined mainly by Marfey’s analysis. Compound 1 exhibited mild toxicity with IC(50)’s of 6.0 µM against the neuron 2a mouse neuroblastoma cells.